(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
This contribution introduces to the video installation Black September (2002) by Swiss artist Christoph Draeger and presents statements of the artist given in an interview in 2012. Draeger collects media representations of disasters in order to reconfigure their inherent sensationalism later in his artworks. The video installation Black September consists of appropriated footage from a documentary movie and video sequences from a re-enactment of the historical events of September 5th 1972, the terrorist attack during the 20th Olympic Games in Munich. Even the artist himself gets involved in the play in his mimikry of a hostage-taker and terrorist. Thus he questions the conditions of the mutual constitution of cultural memory and collective memory. His video installation creates a “counter image” in reaction to the “omnipresent myth of terrorism”, generated by the tragedy of 9/11 and the media reports in its aftermath. Both terrorist attacks, in Munich 1972 and in New York 2001, mark a turning point in the visual dominance of terrorism. In the case of September 11th, the recurring images of the airplane-attacks and the explosion of the WTC, followed by its collapsing, symbolize the legacy of the “terror of attention”, that would affect every spectator. The video questions the limits of the “disaster zone” in fictional reality and mass media. The artwork re-creates central scenes of the event in 1972. It brings the terrorist action close to the spectator through emersive images, but technically obtains a critical distance through its mode of reflection upon the catastrophe.The installation Black September stimulates and simulates history and memory simultaneously. It fills the void of a traumatic narrative and tries to recapture the signs that have been unknown yet.